Towards Gender Equality in Law An Analysis of State Failures from a Global Perspective - Guney, Gizem; Davies, David; Lee, Po-Han (Springer Nature, 2022)
This Open Access book aims to find out how and why states in various regions and of diverse cultural backgrounds fail in their gender equality laws and policies. In doing this, the book maps out states' failures in their legal systems and unpacks the clashes between different levels and forms of law-namely domestic laws, local regulations, or the implementation of international law, individually or in combination. By taking off from the confirmation that the concept of law that is to be used in achieving gender equality is a multidimensional, multi-layered, and to an extent, contradictory phenomenon, this book aims to find out how different layers of laws interact and how they impact gender equality. Further to that, by including different states and jurisdictions into its analysis, this book unravels whether there are any similarities/patterns in how these states define and utilise policies and laws that harm gender equality. In this way, the book contributes to the efforts to devise holistic and universal policies to address various forms of gender inequalities across the world. This volume will be of interest to scholars and students in Gender Studies, Sociology, Law, and Criminology.